Analisis Pengaruh Public Relation dan Sales Promotion Terhadap Minat Beli Pada Produk Starbucks di Kota Bogor - Ardhi Maulana; Mumuh Mulyana (Jurnal Ilmiah Manajemen Kesatuan, 2020)
Technology and industry in Indonesia grow very rapidly and have an impact on changing lifestyle of the community which becomes easier, faster and more economical. So this is what cause the community to be very spoiled by all the conveniences of today’s development. However, the rapid growth of thr coffeeshop business lately has incrased competition. So that demand evey company engage in this industry must pay attention to and balance every need and desire of customer expectations so that statisfaction and trust can always be created which can ultimately lead to puchace interest. Therefore, it is important to conduct research to determne how the influence of public relation and sales promotion on buying interest in Starbucks products. The purpose of this study was to determine the effect of each indicator of Public Relation and Indicator of Sales Promotion on Purchase Interest in Starbucks product. This research uses quaanttative methods and data collection is done by distributing questioners online, to people who know Starbuck but have never bought, with a total sample of 100 people. With technical analysis using the Structural Equation Model (SEM). Which is processed using the AMOS 25 program. The result obtained in this study are variables Public Relation and Sales promotion have a positive and significant effect purchase intention. Keywords : public relation, sales promotion and purchase intention